Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the quadratic equation with roots [tex]\(x = 2 + i\)[/tex] and [tex]\(x = 2 - i\)[/tex], follow these steps:
1. Identify the Roots:
The given roots are [tex]\( x = 2 + i \)[/tex] and [tex]\( x = 2 - i \)[/tex].
2. Form the Factors of the Roots:
The quadratic equation with these roots can be formed by setting up the factors:
[tex]\[ (x - (2 + i))(x - (2 - i)) = 0 \][/tex]
3. Simplify the Expression:
Rewrite the expression to distribute and simplify it step-by-step:
[tex]\[ (x - 2 - i)(x - 2 + i) \][/tex]
This can be seen as a product of a sum and difference of terms:
[tex]\[ [(x - 2) - i][(x - 2) + i] \][/tex]
4. Apply the Difference of Squares Formula:
Using the formula [tex]\((a - b)(a + b) = a^2 - b^2\)[/tex] where [tex]\(a = x - 2\)[/tex] and [tex]\(b = i\)[/tex], we get:
[tex]\[ (x - 2)^2 - (i)^2 \][/tex]
Since [tex]\(i^2 = -1\)[/tex]:
[tex]\[ (x - 2)^2 - (-1) \][/tex]
Simplifying this gives:
[tex]\[ (x - 2)^2 + 1 \][/tex]
5. Expand [tex]\((x - 2)^2\)[/tex]:
Expand the binomial:
[tex]\[ (x - 2)^2 = x^2 - 4x + 4 \][/tex]
6. Form the Quadratic Equation:
Substitute back into the equation:
[tex]\[ (x - 2)^2 + 1 = x^2 - 4x + 4 + 1 = x^2 - 4x + 5 \][/tex]
Thus, the quadratic equation with the roots [tex]\(x = 2 + i\)[/tex] and [tex]\(x = 2 - i\)[/tex] is:
[tex]\[ x^2 - 4x + 5 = 0 \][/tex]
So, the correct quadratic equation is:
[tex]\(\boxed{x^2 - 4x + 5 = 0}\)[/tex]
1. Identify the Roots:
The given roots are [tex]\( x = 2 + i \)[/tex] and [tex]\( x = 2 - i \)[/tex].
2. Form the Factors of the Roots:
The quadratic equation with these roots can be formed by setting up the factors:
[tex]\[ (x - (2 + i))(x - (2 - i)) = 0 \][/tex]
3. Simplify the Expression:
Rewrite the expression to distribute and simplify it step-by-step:
[tex]\[ (x - 2 - i)(x - 2 + i) \][/tex]
This can be seen as a product of a sum and difference of terms:
[tex]\[ [(x - 2) - i][(x - 2) + i] \][/tex]
4. Apply the Difference of Squares Formula:
Using the formula [tex]\((a - b)(a + b) = a^2 - b^2\)[/tex] where [tex]\(a = x - 2\)[/tex] and [tex]\(b = i\)[/tex], we get:
[tex]\[ (x - 2)^2 - (i)^2 \][/tex]
Since [tex]\(i^2 = -1\)[/tex]:
[tex]\[ (x - 2)^2 - (-1) \][/tex]
Simplifying this gives:
[tex]\[ (x - 2)^2 + 1 \][/tex]
5. Expand [tex]\((x - 2)^2\)[/tex]:
Expand the binomial:
[tex]\[ (x - 2)^2 = x^2 - 4x + 4 \][/tex]
6. Form the Quadratic Equation:
Substitute back into the equation:
[tex]\[ (x - 2)^2 + 1 = x^2 - 4x + 4 + 1 = x^2 - 4x + 5 \][/tex]
Thus, the quadratic equation with the roots [tex]\(x = 2 + i\)[/tex] and [tex]\(x = 2 - i\)[/tex] is:
[tex]\[ x^2 - 4x + 5 = 0 \][/tex]
So, the correct quadratic equation is:
[tex]\(\boxed{x^2 - 4x + 5 = 0}\)[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.